Effect of T-stress on the initial fracture toughness of concrete under I/II mixed-mode loading. (August 2018) - Zhao, Yanhua; Dong, Wei; Xu, Bohan; Liu, Jin
Highlights: SIFs and T -stress at the crack tip are computed for four-point bending beam. Negative T -stress can enhance mixed-mode fracture toughness of concrete. Pure II fracture mode with K I and T -stress equal to zero is not easy to achieve. Abstract: The mixed-mode stress intensity factors (SIFs) and T -stress for different geometries of four-point bending specimens were calculated by means of finite element analysis through a software suite Abaqus, where the influence of the crack length, loading point and crack location were considered. Thereafter, a series of four-point bending tests were re-interpreted to account for the consequences of the T -stress on the initial fracture of concrete, where a generalized maximum tangential stress (MTS) criterion was employed. The results indicate that the inclusion of T -stress is essential to predict a more realistic initial fracture toughness of concrete subjected to mixed-mode I/II loading.